(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The current study aimed to identify the relationship between psychological empowerment and professional decision-making among a sample of third-year secondary school students in the city of Jeddah, and to reveal differences between the sample members in the degree of psychological empowerment and professional decision-making according to the variable (gender). The researcher used the descriptive correlational approach, and a sample was formed. The study included (121) male and female students, and used the psychological empowerment scale prepared by Al-Hazmi (2021), and the professional decision-making scale prepared by Hamouda (2017), and the results of the study resulted in the following results: There is a statistically significant direct correlation between psychological empowerment and professional decision-making among the study sample. There are statistically significant differences in the average scores of psychological empowerment and professional decision-making among secondary school students in favor of females. In light of the results, the researcher presented some future recommendations and proposals, including: enhancing the development of self-efficacy for professional decisions among students through conducting guidance programs to develop psychological empowerment at various educational levels, to help them make effective decisions related to difficult life situations in general, and regarding their professional choice in general. In particular, designing training and guidance programs to develop psychological empowerment skills among students at various stages of education.